The combined effects of neurostimulation and priming on creative thinking. A preliminary tDCS study on dorsolateral prefrontal cortex - Colombo, Barbara; Bartesaghi, Noemi; Simonelli, Luisa; Antonietti, Alessandro (Frontiers in Human Neuroscience, 2015)
The role of prefrontal cortex (PFC) in influencing creative thinking has been investigated by many researchers who, while succeeding in proving an effective involvement of PFC, reported suggestive but sometimes conflicting results. In order to better understand the relationships between creative thinking and brain activation in a more specific area of the PFC, we explored the role of dorsolateral PFC. We devised an experimental protocol using transcranial direct-current stimulation (tDCS). The study was based on a 3 (kind of stimulation: anodal vs. cathodal vs. sham) X 2 (priming: divergent vs. convergent) design. Forty-five healthy adults were randomly assigned to one stimulation condition. Participants’ creativity skills were assessed using the Product Improvement subtest from the Torrance Tests of Creative Thinking. After 20 minutes of tDCS stimulation, participants were presented with visual images of common objects. Half of the participants were instructed to visualize themselves using the object in an unusual way (divergent priming), whereas the other half were asked to visualize themselves while using the object in a common way (convergent priming). Priming was aimed at inducing participants to adopt different attitudes toward the creative task. Afterwards, participants were asked to describe all of the possible uses of the objects that were presented. Participants’ physiological activation was recorded using a biofeedback equipment. Results showed a significant effect of anodal stimulation that enhanced creative performance, but only after divergent priming. Participants showed lower skin temperature values after cathodal stimulation, a findings which is coherent with studies reporting that, when a task is not creative or creative thinking is not prompted, people show lower levels of arousal. The involvement of dorsolateral PFC in creativity has been supported, presumably in association to shift of attention modulated by priming.